The Involvement of Phospholipases A2 in Asthma and Chronic Obstructive Pulmonary Disease - Ewa Pniewska; Rafal Pawliczak (Hindawi Limited, 2013)
The increased morbidity, mortality, and ineffective treatment associated with the pathogenesis of chronic inflammatory diseases such as asthma and chronic obstructive pulmonary disease (COPD) have generated much research interest. The key role is played by phospholipases from the A2 superfamily: enzymes which are involved in inflammation through participation in pro- and anti-inflammatory mediators production and have an impact on many immunocompetent cells. The 30 members of the A2 superfamily are divided into 7 groups. Their role in asthma and COPD has been studied in vitro and in vivo (animal models, cell cultures, and patients). This paper contains complete and updated information about the involvement of particular enzymes in the etiology and course of asthma and COPD.